A corrosion-resistant, high-temperature-resistant and high-heat-conductivity material based on polyetheretherketone, a preparation method and a mold
By combining carbon nanotubes with modified polyether sulfone and using them with modified silicon carbide nanowires, polytetrafluoroethylene powder and silicone resin, the problem of poor thermal conductivity of polyether ether ketone materials is solved, which significantly improves its Thermal conductivity and mechanical properties are suitable for high-demand mold applications.
Patent Information
- Application Number
- CN202411281762.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-13
AI Technical Summary
During use, due to poor thermal conductivity of polyether ether ketone materials, the heat generated by friction cannot be quickly exported, resulting in aging of the material and affecting normal use.
By combining carbon nanotubes with modified polyether sulfone, combined with modified silicon carbide nanowires, polytetrafluoroethylene micropowder and silicone resin, and mixing them with polyether ether ketone, their thermal conductivity and mechanical properties are improved.
It significantly improves the thermal conductivity and mechanical properties of the material, enhances its corrosion, heat and wear resistance, making it suitable for applications such as molds and other high-demand applications.
Smart Images

Figure CN118791827B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a corrosion-resistant, high-temperature-resistant and high-heat-conductivity material based on polyetheretherketone, a preparation method and a mold. Background Art
[0002] Polyetheretherketone is a semi-crystalline thermoplastic special engineering plastic. Its special molecular segment structure gives polyetheretherketone excellent comprehensive properties such as excellent high temperature resistance, corrosion resistance, flame retardancy, and wear resistance. It is widely used in various fields; but due to the high friction coefficient, low thermal conductivity and poor thermal conductivity of polyetheretherketone, the heat generated by friction cannot be quickly discharged during use. Long-term heat accumulation will accelerate the aging of polyetheretherketone materials and affect normal use.
[0003] Prior art, such as Chinese patent application CN107459770A, discloses a high thermal conductivity polyetheretherketone composite material and its preparation method, which forms a thermal conductive network by using polyetheretherketone as a matrix and compounding silicon carbide, boron nitride and basalt fiber as thermal conductive fillers. The obtained composite material has the characteristics of high thermal conductivity, high strength and high stability. However, the thermal conductive fillers used are all inorganic thermal conductive fillers, which have poor compatibility with the polymer resin polyetheretherketone, and only physical mixing will affect the mechanical properties of the material. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a corrosion-resistant, high-temperature-resistant and high-heat-conductivity material, a preparation method and a mold based on polyetheretherketone. The material has good corrosion resistance, heat resistance and thermal conductivity, mechanical properties, wear resistance, and can be used in molds.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a corrosion-resistant, high-temperature-resistant and high-heat-conductivity material based on polyetheretherketone comprises the following steps:
[0007] Step (1), dissolving the modified polyethersulfone, chloroform and methanol at room temperature, adding the carbon nanotube suspension, stirring and mixing, casting into a film, shearing and crushing, and drying to obtain a carbon nanotube / modified polyethersulfone composite material;
[0008] Wherein, the preparation of modified polyether sulfone comprises the following steps:
[0009] S11, mixing biphenol, allyl bromide, N,N-dimethylformamide and potassium carbonate, reacting, washing, filtering and drying after the reaction to obtain a reaction product;
[0010] The reaction product is further reacted, and after the reaction is completed, it is recrystallized, filtered, and dried to obtain alkenyl biphenol;
[0011] S12, mixing 4,4'-difluorodiphenyl sulfone with concentrated sulfuric acid, adding N-bromosuccinimide, reacting, and after the reaction is completed, purifying and drying to obtain brominated difluorodiphenyl sulfone;
[0012] Bromodifluorodiphenyl sulfone, 1-pyrene boric acid, potassium phosphate, palladium acetate, triphenylphosphine and toluene are mixed and reacted. After the reaction is completed, the solvent toluene is removed by rotary evaporation to obtain a reaction product, and the organic phase is extracted and passed through a column to obtain pyrenyldifluorodiphenyl sulfone;
[0013] S13, mixing alkenyl biphenol, biphenol, pyrenyl difluorodiphenyl sulfone, potassium carbonate, N-methyl pyrrolidone and toluene, stirring and reacting, and after the reaction is completed, washing and drying to obtain modified polyether sulfone;
[0014] Step (2), uniformly mixing the modified silicon carbide nanowires, polytetrafluoroethylene powder, silicone resin, carbon nanotube / modified polyethersulfone composite material, and polyetheretherketone, reacting, melt-extruding, and granulating to obtain a corrosion-resistant, high-temperature-resistant, and high-heat-conductivity material based on polyetheretherketone;
[0015] The preparation of modified silicon carbide nanowires includes the following steps: mixing silicon carbide nanowires, ethanol and titanate silane coupling agent, ultrasonically dispersing and reacting, and after the reaction is completed, filtering, washing and drying to obtain modified silicon carbide nanowires.
[0016] Preferably, in step (1), the mass ratio of modified polyethersulfone, chloroform, methanol and carbon nanotube suspension is 10:140-150:1-1.8:18-20, and the carbon nanotube suspension is prepared by mixing carbon nanotubes and chloroform in a mass ratio of 1:5; and the stirring and mixing conditions are: stirring and mixing at a speed of 250-300 r / min for 0.5-1 h.
[0017] Preferably, when preparing modified polyethersulfone in step (1), in S11: the mass ratio of biphenyl diphenol, allyl bromide, N,N-dimethylformamide and potassium carbonate is 18-19:25-28:380-430:50-55; the reaction conditions are: reacting at a temperature of 100-110°C for 8-10h.
[0018] Preferably, the washing operation comprises: adding water and ethanol in an amount of 6-8 times the mass of the crude reaction product in sequence to the crude reaction product obtained after the reaction is completed, and washing at room temperature.
[0019] Preferably, when preparing modified polyethersulfone in step (1), in S11: the reaction conditions are: reacting at a temperature of 208-210° C. in a nitrogen atmosphere for 0.5-1 h.
[0020] Preferably, the recrystallization operation comprises: cooling to 110-115° C., adding n-heptane 6-8 times the mass of the reaction product for recrystallization for 18-20 hours.
[0021] Preferably, when preparing modified polyether sulfone in step (1), in S12: the mass ratio of 4,4'-difluorodiphenyl sulfone, concentrated sulfuric acid and N-bromosuccinimide is 1.2-1.25:45-46:1.9-1.95, and the concentrated sulfuric acid is 98wt% concentrated sulfuric acid; the addition time of N-bromosuccinimide is to add it in batches within 2-3h; when preparing brominated difluorodiphenyl sulfone, the reaction conditions are: react at room temperature for 6-8h.
[0022] Preferably, the purification operation comprises: adding 0°C ice water in an amount of 8-10 times the mass of the reaction product to the reaction product obtained after the reaction is completed, standing for 0.5-1h, filtering, taking the filter cake, and adding water in an amount of 5-8 times the mass of the filter cake to wash it.
[0023] Preferably, when preparing modified polyether sulfone in step (1), in S12: the mass ratio of brominated difluorodiphenyl sulfone, 1-pyrene boric acid, potassium phosphate, palladium acetate, triphenylphosphine, and toluene is 5.3-5.5:8.3-8.5:11-12:0.3-0.31:0.7-0.71:60-80; when preparing pyrene difluorodiphenyl sulfone, the reaction conditions are: reacting at a temperature of 90-100° C. for 20-24 hours.
[0024] Preferably, the extraction operation comprises: sequentially adding 2-3 times the amount of water and dichloromethane as much as the reaction product for extraction; and the eluent in the column operation is prepared by mixing ethyl acetate and petroleum ether in a volume ratio of 1:5.
[0025] Preferably, when preparing modified polyethersulfone in step (1), in S13: the mass ratio of alkenyl biphenol, biphenol, pyrenyl difluorodiphenyl sulfone, potassium carbonate, N-methyl pyrrolidone, and toluene is 1.8-2.2:5.6-5.9:18-18.2:5.8-6:50-60:25-30; the reaction conditions are: reacting in a nitrogen atmosphere at a temperature of 130-140°C for 3-4h; and the continued reaction conditions are: continuing the reaction at a temperature of 160-170°C for 10-14h.
[0026] Preferably, in step (2), the mass ratio of modified silicon carbide nanowires, polytetrafluoroethylene powder, silicone resin, carbon nanotube / modified polyethersulfone composite material, and polyetheretherketone is 10-15:10-12:3-5:10-15:110; the reaction conditions are: reaction at a temperature of 345-350°C for 30-40min; and the melt extrusion conditions are: melt extrusion through a twin-screw extruder at a speed of 150-160r / min and a temperature of 355-365°C.
[0027] Preferably, in the step (2) of preparing the modified silicon carbide nanowires, the mass ratio of silicon carbide nanowires, ethanol and titanate silane coupling agent is 10:300-350:0.8-1; and the reaction conditions are: reacting at a temperature of 80-100° C. for 1-2 hours.
[0028] Preferably, a corrosion-resistant, high-temperature-resistant, and high-heat-transfer material based on polyetheretherketone is prepared by the method for preparing the corrosion-resistant, high-temperature-resistant, and high-heat-transfer material based on polyetheretherketone as described above.
[0029] Preferably, a corrosion-resistant, high-temperature-resistant and high-heat-conductivity material based on polyetheretherketone as described above is used on a mold.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The present invention prepares a carbon nanotube / modified polyethersulfone composite material prepared by compounding carbon nanotubes and modified polyethersulfone, and adds the carbon nanotube / modified polyethersulfone composite material together with modified silicon carbide nanowires, polytetrafluoroethylene powder and silicone resin into polyetheretherketone, thereby improving the thermal conductivity and mechanical properties of polyetheretherketone. The prepared material has good corrosion resistance and heat resistance and thermal conductivity, as well as excellent mechanical properties and wear resistance, and can be used in molds.
[0032] The invention mixes biphenol and allyl bromide to undergo a nucleophilic substitution reaction, and after the reaction, the reaction product is further reacted under high temperature conditions to make the allyl group migrate from the oxygen atom to the carbon atom, and Claisen rearrangement occurs to obtain alkenyl biphenol; 4,4'-difluorodiphenyl sulfone is brominated with N-bromosuccinimide to obtain brominated difluorodiphenyl sulfone, and the brominated difluorodiphenyl sulfone is subjected to a Suzuki coupling reaction with 1-pyrene boric acid under catalyst conditions to introduce a pyrene group with a planar macroconjugated structure on the side chain of 4,4'-difluorodiphenyl sulfone. , obtaining pyrene difluorodiphenyl sulfone; subjecting alkenyl biphenol, biphenol and pyrene difluorodiphenyl sulfone to polycondensation reaction under the action of a catalyst to obtain a modified polyether sulfone having alkenyl and pyrene groups in the side chain; compounding the modified polyether sulfone with carbon nanotubes as a thermal conductive functional filler to obtain a carbon nanotube / modified polyether sulfone composite material; adding the carbon nanotube / modified polyether sulfone composite material together with silicon carbide nanowires modified with a titanate silane coupling agent, polytetrafluoroethylene micropowder and silicone resin to polyether ether ketone to obtain a corrosion-resistant, high-temperature-resistant and high-heat-conductivity material based on polyether ether ketone;
[0033] Among them, polytetrafluoroethylene powder can improve the tribological properties of polyetheretherketone, silicone resin acts as a toughening agent to improve the mechanical properties of the matrix, and carbon nanotubes and modified silicon carbide nanowires synergistically improve the thermal conductivity and heat transfer properties of the material; the side chain of modified polyethersulfone has alkenyl and pyrene groups, and the pyrene group can utilize π-π conjugation to non-covalently modify the carbon nanotubes, so that the carbon nanotubes are evenly dispersed in the polyethersulfone matrix resin and reduce agglomeration. Moreover, due to the good compatibility of polyethersulfone and polyetheretherketone, the modified polyethersulfone forms an interface layer between the carbon nanotubes and the polyetheretherketone, thereby improving the dispersion of the carbon nanotubes in the polyetheretherketone matrix; the side chain alkenyl groups of the modified polyethersulfone can undergo cross-linking under high temperature conditions, construct a cross-linking network in the polyetheretherketone matrix, and further improve the heat resistance, corrosion resistance and mechanical properties of polyetheretherketone. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a process flow chart for preparing a corrosion-resistant, high-temperature-resistant and high-heat-conductivity material based on polyetheretherketone in the present invention;
[0035] Figure 2 It is a friction coefficient bar graph of comprehensive performance test of corrosion-resistant, high-temperature-resistant and high-heat-transfer materials based on polyetheretherketone prepared in Examples 1-5 and Comparative Examples 1-2 of the present invention;
[0036] Figure 3 It is a bar graph of thermal conductivity in comprehensive performance test of corrosion-resistant, high-temperature-resistant and high heat transfer materials based on polyetheretherketone prepared in Examples 1-5 and Comparative Examples 1-2 of the present invention. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] like Figure 1 As shown, this embodiment discloses a method for preparing a corrosion-resistant, high-temperature-resistant and high heat transfer material based on polyetheretherketone, comprising the following steps:
[0040] Step (1), mixing and dissolving modified polyethersulfone, chloroform and methanol at room temperature, adding carbon nanotube suspension, wherein the mass ratio of modified polyethersulfone, chloroform, methanol and carbon nanotube suspension is 10:140:1:18, the carbon nanotube suspension is prepared by mixing carbon nanotubes and chloroform in a mass ratio of 1:5, stirring at a speed of 250 r / min for 1 hour, casting into a film, shearing and crushing, and drying at a temperature of 50° C. for 24 hours to obtain a carbon nanotube / modified polyethersulfone composite material;
[0041] Wherein, the preparation of modified polyether sulfone comprises the following steps:
[0042] S11, mixing biphenol, allyl bromide, N,N-dimethylformamide and potassium carbonate in a mass ratio of 18:25:380:50, reacting at 100°C for 10 hours, and after the reaction, obtaining a crude reaction product, adding water and ethanol 6 times the mass of the crude reaction product in sequence, washing at room temperature, filtering, taking a filter cake, and drying at 50°C for 10 hours to obtain a reaction product;
[0043] The reaction product was reacted in a nitrogen atmosphere at 208°C for 1 hour. After the reaction, it was cooled to 110°C, and n-heptane with a mass 6 times that of the reaction product was added for recrystallization for 18 hours. After recrystallization, it was filtered, and the filter cake was taken and dried at 50°C for 12 hours to obtain alkenyl biphenol.
[0044] S12, 4,4'-difluorodiphenyl sulfone was mixed with 98wt% concentrated sulfuric acid, and N-bromosuccinimide was added in portions within 2h, the mass ratio of 4,4'-difluorodiphenyl sulfone, 98wt% concentrated sulfuric acid, and N-bromosuccinimide was 1.2:45:1.9, and the mixture was reacted at room temperature for 6h. After the reaction was completed, a reaction product was obtained, 8 times the mass of the reaction product was added with 0°C ice water, and the mixture was allowed to stand for 0.5h, and filtered, a filter cake was taken, and 5 times the mass of the filter cake was added with water for washing, and the mixture was dried at 40°C for 22h to obtain brominated difluorodiphenyl sulfone;
[0045] Bromodifluorodiphenyl sulfone, 1-pyrene boric acid, potassium phosphate, palladium acetate, triphenylphosphine and toluene were mixed in a mass ratio of 5.3:8.3:11:0.3:0.7:60, and reacted at 90°C for 24 hours. After the reaction, the solvent toluene was removed by rotary evaporation at 80°C to obtain a reaction product, and water and dichloromethane, which were twice the amount of the reaction product, were added in sequence for extraction, and the organic phase was taken and passed through a column to obtain pyrenyldifluorodiphenyl sulfone;
[0046] The eluent in the column operation is prepared by mixing ethyl acetate and petroleum ether in a volume ratio of 1:5;
[0047] S13, alkenyl biphenol, biphenol, pyrenyl difluorodiphenyl sulfone, potassium carbonate, N-methyl pyrrolidone, and toluene were mixed and stirred at a mass ratio of 1.8:5.9:18:5.8:50:25 at room temperature for 20 minutes, reacted at 130°C in a nitrogen atmosphere for 4 hours, and after the reaction was completed, continued to react at 160°C for 14 hours. After the reaction was completed, a reaction product was obtained, ethanol in an amount of 8 times the mass of the reaction product was added, filtered, and the filter cake was taken and dried at 70°C for 24 hours to obtain a modified polyether sulfone;
[0048] Step (2), uniformly mixing modified silicon carbide nanowires, polytetrafluoroethylene powder, silicone resin, carbon nanotube / modified polyethersulfone composite material, and polyetheretherketone at a mass ratio of 15:10:5:10:110, reacting at 345°C for 30 minutes, and melt-extruded through a twin-screw extruder at a speed of 150 r / min and a temperature of 355°C, and granulated to obtain a corrosion-resistant, high-temperature-resistant, and high-heat-conductivity material based on polyetheretherketone;
[0049] Among them, the preparation of modified silicon carbide nanowires includes the following steps: mixing silicon carbide nanowires, ethanol, and titanate silane coupling agent in a mass ratio of 10:300:0.8, ultrasonically dispersing for 20 minutes, reacting at 80°C for 2 hours, filtering after the reaction, taking the filter cake, adding ethanol 6 times the mass of the filter cake for washing, and drying at 60°C for 10 hours to obtain modified silicon carbide nanowires.
[0050] Example 2
[0051] This embodiment discloses a method for preparing a corrosion-resistant, high-temperature-resistant and high heat transfer material based on polyetheretherketone, comprising the following steps:
[0052] Step (1), mixing and dissolving modified polyethersulfone, chloroform and methanol at room temperature, adding carbon nanotube suspension, wherein the mass ratio of modified polyethersulfone, chloroform, methanol and carbon nanotube suspension is 10:143:1.2:18.5, the carbon nanotube suspension is prepared by mixing carbon nanotubes and chloroform in a mass ratio of 1:5, stirring at a speed of 270 r / min for 0.8 h, casting into a film, shearing and crushing, and drying at a temperature of 55° C. for 22 h to obtain a carbon nanotube / modified polyethersulfone composite material;
[0053] Wherein, the preparation of modified polyether sulfone comprises the following steps:
[0054] S11, mixing biphenol, allyl bromide, N,N-dimethylformamide and potassium carbonate in a mass ratio of 18.3:26:400:52, reacting at 105°C for 9 hours, and after the reaction, obtaining a crude reaction product, adding water and ethanol in an amount of 6 times the mass of the crude reaction product in sequence, washing at room temperature, filtering, taking a filter cake, and drying at 55°C for 9 hours to obtain a reaction product;
[0055] The reaction product was reacted in a nitrogen atmosphere at 208°C for 0.8h. After the reaction, it was cooled to 110°C, and n-heptane with a mass 7 times that of the reaction product was added for recrystallization for 19h. After recrystallization, it was filtered, the filter cake was taken, and dried at 55°C for 11h to obtain alkenyl biphenol;
[0056] S12, 4,4'-difluorodiphenyl sulfone was mixed with 98wt% concentrated sulfuric acid, and N-bromosuccinimide was added in portions within 2.5h, the mass ratio of 4,4'-difluorodiphenyl sulfone, 98wt% concentrated sulfuric acid, and N-bromosuccinimide was 1.21:45.3:1.91, and the mixture was reacted at room temperature for 7h. After the reaction was completed, a reaction product was obtained, 9 times the mass of the reaction product was added with 0°C ice water, and the mixture was allowed to stand for 0.8h, and filtered, a filter cake was taken, and 6 times the mass of the filter cake was added with water for washing, and the mixture was dried at 45°C for 20h to obtain brominated difluorodiphenyl sulfone;
[0057] Bromodifluorodiphenyl sulfone, 1-pyrene boric acid, potassium phosphate, palladium acetate, triphenylphosphine and toluene were mixed in a mass ratio of 5.35:8.35:11.3:0.3:0.7:70, and reacted at 95°C for 22 hours. After the reaction, the solvent toluene was removed by rotary evaporation at 85°C to obtain a reaction product, and water and dichloromethane, which were twice the amount of the reaction product, were added in sequence for extraction, and the organic phase was taken and passed through a column to obtain pyrenyldifluorodiphenyl sulfone;
[0058] The eluent in the column operation is prepared by mixing ethyl acetate and petroleum ether in a volume ratio of 1:5;
[0059] S13, alkenyl biphenol, biphenol, pyrenyl difluorodiphenyl sulfone, potassium carbonate, N-methyl pyrrolidone, and toluene were mixed and stirred at a mass ratio of 1.9:5.8:18.1:5.85:53:26 at room temperature for 25 minutes, reacted at 130°C in a nitrogen atmosphere for 3.5 hours, and after the reaction was completed, continued to react at 160°C for 12 hours. After the reaction was completed, a reaction product was obtained, ethanol 8 times the mass of the reaction product was added, filtered, and the filter cake was taken and dried at 75°C for 22 hours to obtain modified polyether sulfone;
[0060] Step (2), uniformly mixing modified silicon carbide nanowires, polytetrafluoroethylene powder, silicone resin, carbon nanotube / modified polyethersulfone composite material, and polyetheretherketone in a mass ratio of 14:10.5:4.5:11:110, reacting at 345°C for 35 minutes, and melt-extruded through a twin-screw extruder at a speed of 155 r / min and a temperature of 360°C, and granulating to obtain a corrosion-resistant, high-temperature-resistant, and high-heat-conductivity material based on polyetheretherketone;
[0061] Among them, the preparation of modified silicon carbide nanowires includes the following steps: mixing silicon carbide nanowires, ethanol, and titanate silane coupling agent in a mass ratio of 10:320:0.85, ultrasonically dispersing for 25 minutes, reacting at 90°C for 1.5 hours, filtering after the reaction, taking the filter cake, adding ethanol 6 times the mass of the filter cake for washing, and drying at 65°C for 9 hours to obtain modified silicon carbide nanowires.
[0062] Example 3
[0063] This embodiment discloses a method for preparing a corrosion-resistant, high-temperature-resistant and high heat transfer material based on polyetheretherketone, comprising the following steps:
[0064] Step (1), mixing and dissolving modified polyethersulfone, chloroform and methanol at room temperature, adding carbon nanotube suspension, wherein the mass ratio of modified polyethersulfone, chloroform, methanol and carbon nanotube suspension is 10:145:1.4:19, the carbon nanotube suspension is prepared by mixing carbon nanotubes and chloroform in a mass ratio of 1:5, stirring at a speed of 270 r / min for 0.8 h, casting into a film, shearing and crushing, and drying at a temperature of 55° C. for 22 h to obtain a carbon nanotube / modified polyethersulfone composite material;
[0065] Wherein, the preparation of modified polyether sulfone comprises the following steps:
[0066] S11, mixing biphenol, allyl bromide, N,N-dimethylformamide and potassium carbonate in a mass ratio of 18.5:26.5:400:53, reacting at 105°C for 9 hours, and after the reaction, obtaining a crude reaction product, adding water and ethanol in an amount of 7 times the mass of the crude reaction product in sequence, washing at room temperature, filtering, taking a filter cake, and drying at 55°C for 9 hours to obtain a reaction product;
[0067] The reaction product was reacted in a nitrogen atmosphere at 209°C for 0.8h. After the reaction, it was cooled to 113°C and recrystallized for 19h by adding n-heptane 7 times the mass of the reaction product. After recrystallization, it was filtered and the filter cake was taken and dried at 55°C for 11h to obtain alkenyl biphenol.
[0068] S12, 4,4'-difluorodiphenyl sulfone was mixed with 98wt% concentrated sulfuric acid, and N-bromosuccinimide was added in portions within 2.5h, the mass ratio of 4,4'-difluorodiphenyl sulfone, 98wt% concentrated sulfuric acid, and N-bromosuccinimide was 1.23:45.5:1.93, and the mixture was reacted at room temperature for 7h. After the reaction was completed, a reaction product was obtained, 9 times the mass of the reaction product was added with 0°C ice water, and the mixture was allowed to stand for 0.8h, and filtered, a filter cake was taken, 6 times the mass of the filter cake was added with water for washing, and the mixture was dried at 45°C for 20h to obtain brominated difluorodiphenyl sulfone;
[0069] Bromodifluorodiphenyl sulfone, 1-pyrene boric acid, potassium phosphate, palladium acetate, triphenylphosphine and toluene were mixed in a mass ratio of 5.4:8.4:11.5:0.3:0.7:70, and reacted at 95°C for 22 hours. After the reaction, the solvent toluene was removed by rotary evaporation at 85°C to obtain a reaction product, and water and dichloromethane, which were twice the amount of the reaction product, were added in sequence for extraction, and the organic phase was taken and passed through a column to obtain pyrenyldifluorodiphenyl sulfone;
[0070] The eluent in the column operation is prepared by mixing ethyl acetate and petroleum ether in a volume ratio of 1:5;
[0071] S13, alkenyl biphenol, biphenol, pyrenyl difluorodiphenyl sulfone, potassium carbonate, N-methyl pyrrolidone, and toluene were mixed and stirred at a mass ratio of 2:5.75:18.1:5.9:55:28 at room temperature for 25 minutes, reacted at 135°C in a nitrogen atmosphere for 3.5 hours, and after the reaction was completed, continued to react at 165°C for 12 hours. After the reaction was completed, a reaction product was obtained, ethanol of 9 times the mass of the reaction product was added, filtered, and the filter cake was taken and dried at 75°C for 22 hours to obtain modified polyether sulfone;
[0072] Step (2), uniformly mixing modified silicon carbide nanowires, polytetrafluoroethylene powder, silicone resin, carbon nanotube / modified polyethersulfone composite material, and polyetheretherketone in a mass ratio of 13:11:4:12:110, reacting at 345°C for 35 minutes, and melt-extruded through a twin-screw extruder at a speed of 155 r / min and a temperature of 360°C, and granulating to obtain a corrosion-resistant, high-temperature-resistant, and high-heat-conductivity material based on polyetheretherketone;
[0073] Among them, the preparation of modified silicon carbide nanowires includes the following steps: mixing silicon carbide nanowires, ethanol, and titanate silane coupling agent in a mass ratio of 10:330:0.9, ultrasonically dispersing for 25 minutes, reacting at 90°C for 1.5 hours, filtering after the reaction, taking the filter cake, adding ethanol 7 times the mass of the filter cake for washing, and drying at 65°C for 9 hours to obtain modified silicon carbide nanowires.
[0074] Example 4
[0075] This embodiment discloses a method for preparing a corrosion-resistant, high-temperature-resistant and high heat transfer material based on polyetheretherketone, comprising the following steps:
[0076] Step (1), mixing and dissolving modified polyethersulfone, chloroform and methanol at room temperature, adding carbon nanotube suspension, wherein the mass ratio of modified polyethersulfone, chloroform, methanol and carbon nanotube suspension is 10:148:1.6:19.5, the carbon nanotube suspension is prepared by mixing carbon nanotubes and chloroform in a mass ratio of 1:5, stirring at a speed of 300 r / min for 0.8 h, casting into a film, shearing and crushing, and drying at a temperature of 55° C. for 22 h to obtain a carbon nanotube / modified polyethersulfone composite material;
[0077] Wherein, the preparation of modified polyether sulfone comprises the following steps:
[0078] S11, mixing biphenol, allyl bromide, N,N-dimethylformamide and potassium carbonate in a mass ratio of 18.8:27:400:54, reacting at 105°C for 9 hours, and after the reaction, obtaining a crude reaction product, adding water and ethanol in an amount of 8 times the mass of the crude reaction product in sequence, washing at room temperature, filtering, taking a filter cake, and drying at 55°C for 9 hours to obtain a reaction product;
[0079] The reaction product was reacted in a nitrogen atmosphere at 210°C for 0.8h. After the reaction, it was cooled to 115°C, and n-heptane with a mass 8 times that of the reaction product was added for recrystallization for 20h. After recrystallization, it was filtered, the filter cake was taken, and dried at 55°C for 11h to obtain alkenyl biphenol;
[0080] S12, 4,4'-difluorodiphenyl sulfone was mixed with 98wt% concentrated sulfuric acid, and N-bromosuccinimide was added in portions within 3h, the mass ratio of 4,4'-difluorodiphenyl sulfone, 98wt% concentrated sulfuric acid, and N-bromosuccinimide was 1.24:45.8:1.94, and the mixture was reacted at room temperature for 8h. After the reaction was completed, a reaction product was obtained, 10 times the mass of the reaction product was added with 0°C ice water, and the mixture was allowed to stand for 0.8h, and filtered, a filter cake was taken, and 6 times the mass of the filter cake was added with water for washing, and the mixture was dried at 45°C for 20h to obtain brominated difluorodiphenyl sulfone;
[0081] Bromodifluorodiphenyl sulfone, 1-pyrene boric acid, potassium phosphate, palladium acetate, triphenylphosphine and toluene were mixed in a mass ratio of 5.45:8.45:11.8:0.31:0.71:70, and reacted at 95°C for 22 hours. After the reaction, the solvent toluene was removed by rotary evaporation at 85°C to obtain a reaction product, and water 3 times the amount of the reaction product and dichloromethane were added in sequence for extraction, and the organic phase was taken and passed through a column to obtain pyrenyldifluorodiphenyl sulfone;
[0082] The eluent in the column operation is prepared by mixing ethyl acetate and petroleum ether in a volume ratio of 1:5;
[0083] S13, alkenyl biphenol, biphenol, pyrenyl difluorodiphenyl sulfone, potassium carbonate, N-methyl pyrrolidone, and toluene were mixed and stirred at a mass ratio of 2.1:5.65:18.1:5.95:58:29 at room temperature for 30 minutes, reacted at 140°C in a nitrogen atmosphere for 3.5 hours, and after the reaction was completed, continued to react at 160°C for 12 hours. After the reaction was completed, a reaction product was obtained, ethanol of 9 times the mass of the reaction product was added, filtered, and the filter cake was taken and dried at 75°C for 22 hours to obtain modified polyether sulfone;
[0084] Step (2), uniformly mixing modified silicon carbide nanowires, polytetrafluoroethylene powder, silicone resin, carbon nanotube / modified polyethersulfone composite material, and polyetheretherketone in a mass ratio of 11:11.5:3.5:14:110, reacting at 350°C for 40 minutes, and melt-extruded through a twin-screw extruder at a speed of 160 r / min and a temperature of 360°C to form pellets, thereby obtaining a corrosion-resistant, high-temperature-resistant, and high-heat-conductivity material based on polyetheretherketone;
[0085] Among them, the preparation of modified silicon carbide nanowires includes the following steps: mixing silicon carbide nanowires, ethanol, and titanate silane coupling agent in a mass ratio of 10:340:0.95, ultrasonically dispersing for 25 minutes, reacting at 90°C for 1.5 hours, filtering after the reaction, taking the filter cake, adding ethanol 7 times the mass of the filter cake for washing, and drying at 65°C for 9 hours to obtain modified silicon carbide nanowires.
[0086] Example 5
[0087] This embodiment discloses a method for preparing a corrosion-resistant, high-temperature-resistant and high heat transfer material based on polyetheretherketone, comprising the following steps:
[0088] Step (1), mixing and dissolving modified polyethersulfone, chloroform and methanol at room temperature, adding carbon nanotube suspension, wherein the mass ratio of modified polyethersulfone, chloroform, methanol and carbon nanotube suspension is 10:150:1.8:20, the carbon nanotube suspension is prepared by mixing carbon nanotubes and chloroform in a mass ratio of 1:5, stirring at a speed of 300 r / min for 0.5 h, casting into a film, shearing and crushing, and drying at a temperature of 60° C. for 20 h to obtain a carbon nanotube / modified polyethersulfone composite material;
[0089] Wherein, the preparation of modified polyether sulfone comprises the following steps:
[0090] S11, mixing biphenol, allyl bromide, N,N-dimethylformamide and potassium carbonate in a mass ratio of 19:28:430:55, reacting at 110°C for 8 hours, and after the reaction, obtaining a crude reaction product, adding water and ethanol 8 times the mass of the crude reaction product in sequence, washing at room temperature, filtering, taking a filter cake, and drying at 60°C for 8 hours to obtain a reaction product;
[0091] The reaction product was reacted in a nitrogen atmosphere at 210° C. for 0.5 h. After the reaction, it was cooled to 115° C., and n-heptane with a mass 8 times that of the reaction product was added for recrystallization for 20 h. After recrystallization, it was filtered, and the filter cake was taken and dried at 60° C. for 10 h to obtain alkenyl biphenol.
[0092] S12, 4,4'-difluorodiphenyl sulfone was mixed with 98wt% concentrated sulfuric acid, and N-bromosuccinimide was added in portions within 3h, the mass ratio of 4,4'-difluorodiphenyl sulfone, 98wt% concentrated sulfuric acid, and N-bromosuccinimide was 1.25:46:1.95, and the mixture was reacted at room temperature for 8h. After the reaction was completed, a reaction product was obtained, 10 times the mass of the reaction product was added with 0°C ice water, and the mixture was allowed to stand for 1h, and the filter cake was taken out by suction, and 8 times the mass of the filter cake was added with water for washing, and the mixture was dried at 50°C for 18h to obtain brominated difluorodiphenyl sulfone;
[0093] Bromodifluorodiphenyl sulfone, 1-pyrene boric acid, potassium phosphate, palladium acetate, triphenylphosphine and toluene were mixed in a mass ratio of 5.5:8.5:12:0.31:0.71:80, and reacted at 100°C for 20 hours. After the reaction, the solvent toluene was removed by rotary evaporation at 90°C to obtain a reaction product, and water 3 times the amount of the reaction product and dichloromethane were added in sequence for extraction, and the organic phase was taken and passed through a column to obtain pyrenyldifluorodiphenyl sulfone;
[0094] The eluent in the column operation is prepared by mixing ethyl acetate and petroleum ether in a volume ratio of 1:5;
[0095] S13, alkenyl biphenol, biphenol, pyrenyl difluorodiphenyl sulfone, potassium carbonate, N-methyl pyrrolidone, and toluene were mixed and stirred at a mass ratio of 2.2:5.6:18.2:6:60:30 at room temperature for 30 minutes, reacted at 140°C in a nitrogen atmosphere for 3 hours, and after the reaction was completed, continued to react at 170°C for 10 hours. After the reaction was completed, a reaction product was obtained, ethanol 10 times the mass of the reaction product was added, filtered, and the filter cake was taken and dried at 80°C for 20 hours to obtain modified polyether sulfone;
[0096] Step (2), uniformly mixing modified silicon carbide nanowires, polytetrafluoroethylene powder, silicone resin, carbon nanotube / modified polyethersulfone composite material, and polyetheretherketone in a mass ratio of 10:12:3:15:110, reacting at 350°C for 40 minutes, and melt-extruded through a twin-screw extruder at a speed of 160 r / min and a temperature of 365°C, and granulated to obtain a corrosion-resistant, high-temperature-resistant, and high-heat-conductivity material based on polyetheretherketone;
[0097] Among them, the preparation of modified silicon carbide nanowires includes the following steps: mixing silicon carbide nanowires, ethanol, and titanate silane coupling agent in a mass ratio of 10:350:1, ultrasonically dispersing for 30 minutes, reacting at 100°C for 1 hour, filtering after the reaction, taking the filter cake, adding ethanol 8 times the mass of the filter cake for washing, and drying at 70°C for 8 hours to obtain modified silicon carbide nanowires.
[0098] Comparative Example 1
[0099] This comparative example discloses a method for preparing a material based on polyetheretherketone, comprising the following steps:
[0100] Silicon carbide nanowires, polytetrafluoroethylene powder, silicone resin, carbon nanotubes, and polyetheretherketone are uniformly mixed in a mass ratio of 15:10:5:3:110, reacted at 345°C for 30 minutes, melt-extruded through a twin-screw extruder at a speed of 150 r / min and a temperature of 355°C, and granulated to obtain a material based on polyetheretherketone.
[0101] Comparative Example 2
[0102] This comparative example discloses a method for preparing a material based on polyetheretherketone, comprising the following steps:
[0103] Step (1), mixing and dissolving modified polyethersulfone, chloroform and methanol at room temperature, adding carbon nanotube suspension, wherein the mass ratio of modified polyethersulfone, chloroform, methanol and carbon nanotube suspension is 10:140:1:18, the carbon nanotube suspension is prepared by mixing carbon nanotubes and chloroform in a mass ratio of 1:5, stirring at a speed of 250 r / min for 1 hour, casting into a film, shearing and crushing, and drying at a temperature of 50° C. for 24 hours to obtain a carbon nanotube / modified polyethersulfone composite material;
[0104] Wherein, the preparation of modified polyether sulfone comprises the following steps:
[0105] S11, mixing biphenol, allyl bromide, N,N-dimethylformamide and potassium carbonate in a mass ratio of 18:25:380:50, reacting at 100°C for 10 hours, and after the reaction, obtaining a crude reaction product, adding water and ethanol 6 times the mass of the crude reaction product in sequence, washing at room temperature, filtering, taking a filter cake, and drying at 50°C for 10 hours to obtain a reaction product;
[0106] The reaction product was reacted in a nitrogen atmosphere at 208°C for 1 hour. After the reaction, it was cooled to 110°C, and n-heptane with a mass 6 times that of the reaction product was added for recrystallization for 18 hours. After recrystallization, it was filtered, and the filter cake was taken and dried at 50°C for 12 hours to obtain alkenyl biphenol.
[0107] S12, 4,4'-difluorodiphenyl sulfone was mixed with 98wt% concentrated sulfuric acid, and N-bromosuccinimide was added in portions within 2h, the mass ratio of 4,4'-difluorodiphenyl sulfone, 98wt% concentrated sulfuric acid, and N-bromosuccinimide was 1.2:45:1.9, and the mixture was reacted at room temperature for 6h. After the reaction was completed, a reaction product was obtained, 8 times the mass of the reaction product was added with 0°C ice water, and the mixture was allowed to stand for 0.5h, and filtered, a filter cake was taken, and 5 times the mass of the filter cake was added with water for washing, and the mixture was dried at 40°C for 22h to obtain brominated difluorodiphenyl sulfone;
[0108] Bromodifluorodiphenyl sulfone, 1-pyrene boric acid, potassium phosphate, palladium acetate, triphenylphosphine and toluene were mixed in a mass ratio of 5.3:8.3:11:0.3:0.7:60, and reacted at 90°C for 24 hours. After the reaction, the solvent toluene was removed by rotary evaporation at 80°C to obtain a reaction product, and water and dichloromethane, which were twice the amount of the reaction product, were added in sequence for extraction, and the organic phase was taken and passed through a column to obtain pyrenyldifluorodiphenyl sulfone;
[0109] The eluent in the column operation is prepared by mixing ethyl acetate and petroleum ether in a volume ratio of 1:5;
[0110] S13, alkenyl biphenol, biphenol, pyrenyl difluorodiphenyl sulfone, potassium carbonate, N-methyl pyrrolidone, and toluene were mixed and stirred at a mass ratio of 1.8:5.9:18:5.8:50:25 at room temperature for 20 minutes, reacted at 130°C in a nitrogen atmosphere for 4 hours, and after the reaction was completed, continued to react at 160°C for 14 hours. After the reaction was completed, a reaction product was obtained, ethanol in an amount of 8 times the mass of the reaction product was added, filtered, and the filter cake was taken and dried at 70°C for 24 hours to obtain a modified polyether sulfone;
[0111] Step (2), mixing the carbon nanotube / modified polyethersulfone composite material, silicone resin and polyetheretherketone in a mass ratio of 10:5:135, reacting at a temperature of 345°C for 30 minutes, and melt-extruded through a twin-screw extruder in a nitrogen atmosphere at a speed of 150 r / min and a temperature of 355°C, and granulating to obtain a polyetheretherketone-based material.
[0112] In the above embodiments and comparative examples: carbon nanotubes are from Guangzhou Hongwu Materials Technology Co., Ltd., product name multi-walled carbon nanotubes, length 5-20 μm, diameter 10-30 nm; biphenyl diphenol is from Jinan Yunuo Chemical Co., Ltd., CAS No.: 92-88-6; allyl bromide is from Hubei Keward Chemical Co., Ltd., CAS No.: 106-95-6; 4,4'-difluorodiphenyl sulfone is from Shandong Xiya Chemical Co., Ltd., CAS No.: 383-29-9; N-bromosuccinimide is from Shandong Xinghai Chemical Co., Ltd., CAS No.: 128-08-5; 1-pyrene boric acid is from Hubei Weideli Chemical Reagent Co., Ltd., CAS No.: 164461-18-1; polytetrafluoroethylene powder is from Solvay Group, USA, model PTFE XPP 535, particle size 3.8μm, CAS number: 9002-84-0; silicone resin comes from Dow Corning, model silicone powder RM4-7051; polyetheretherketone comes from Victrex, UK, model PEEK 150G; silicon carbide nanowires come from Zhongke Leiming (Beijing) Technology Co., Ltd., product name one-dimensional silicon carbide nanowires, length 50μm, diameter 100nm; titanate silane coupling agent comes from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., model titanate silane coupling agent NDZ201.
[0113] Test example
[0114] like Figure 2-3 As shown, comprehensive performance tests were conducted on the polyetheretherketone-based materials prepared in Examples 1-5 and Comparative Examples 1-2. The specific test results are shown in Table 1:
[0115] Table 1
[0116]
[0117] The detection of each index in Table 1 is respectively based on the following standards: tensile strength is measured with reference to GB / T1040-1992 "Test Method for Tensile Properties of Plastics"; friction coefficient is measured with reference to GB / T 3960-1989 "Test Method for Sliding Friction and Wear of Plastics"; corrosion resistance test includes: the polyetheretherketone-based materials prepared in Examples 1-5 and Comparative Examples 1-2 are prepared into test specimens with reference to GB / T1040-1992 "Test Method for Tensile Properties of Plastics", recorded as samples 1-7, samples 1-7 are respectively immersed in 30wt% sodium hydroxide aqueous solution and 30wt% sulfuric acid aqueous solution for 20 days, and the changes in the apparent and tensile strength of the samples are recorded.
[0118] It can be seen from the test results in Table 1 that the polyetheretherketone-based material prepared in the present invention has good corrosion resistance and heat resistance and thermal conductivity, as well as excellent mechanical properties.
[0119] The present invention prepares a modified polyethersulfone having alkenyl and pyrene groups on the side chain, and composites the modified polyethersulfone with carbon nanotubes as heat-conducting functional fillers to obtain a carbon nanotube / modified polyethersulfone composite material, and adds the carbon nanotube / modified polyethersulfone composite material together with silicon carbide nanowires modified by a titanate silane coupling agent, polytetrafluoroethylene micropowder, and silicone resin into polyetheretherketone to obtain a corrosion-resistant, high-temperature-resistant, and high-heat-conductivity material based on polyetheretherketone; wherein the polytetrafluoroethylene micropowder can improve the tribological properties of the polyetheretherketone, the silicone resin can be used as a toughening agent to improve the mechanical properties of the matrix, and the carbon nanotubes and the modified silicon carbide nanowires can synergistically improve the conductivity of the material. Thermal transfer performance; the side chain of modified polyethersulfone has alkenyl and pyrene groups, and the pyrene groups can utilize π-π conjugation to non-covalently modify carbon nanotubes, so that the carbon nanotubes are evenly dispersed in the polyethersulfone matrix resin and the agglomeration phenomenon is reduced. In addition, due to the good compatibility of polyethersulfone and polyetheretherketone, the modified polyethersulfone forms an interface layer between the carbon nanotubes and the polyetheretherketone, thereby improving the dispersion of the carbon nanotubes in the polyetheretherketone matrix. The side chain alkenyl groups of the modified polyethersulfone can cross-link under high temperature conditions, construct a cross-linking network in the polyetheretherketone matrix, and further improve the heat resistance, corrosion resistance and mechanical properties of polyetheretherketone.
[0120] In Comparative Example 1, the carbon nanotubes and silicon carbide nanowires are not surface modified, the dispersion of the carbon nanotubes in the polyetheretherketone matrix is reduced, and they are easily agglomerated, which affects the thermal conductivity of the matrix. At the same time, there is a lack of modified polyethersulfone side chain alkenyl groups to form a cross-linked network under high temperature conditions, so the thermal conductivity and mechanical properties of Comparative Example 2 are lower than those of the embodiment;
[0121] In Comparative Example 2, no modified silicon carbide nanowires and polytetrafluoroethylene powder were added, the friction coefficient of the material increased, the wear resistance decreased, and there was a lack of modified silicon carbide nanowires and carbon nanotubes to synergistically improve the thermal conductivity of the matrix, so the wear resistance and thermal conductivity of Comparative Example 2 were lower than those of the embodiment.
[0122] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a corrosion-resistant, high-temperature-resistant and high-heat-conductivity material based on polyetheretherketone, characterized in that: The following steps are involved: Step (1), dissolving the modified polyethersulfone, chloroform and methanol at room temperature, adding the carbon nanotube suspension, stirring and mixing, casting into a film, shearing and crushing, and drying to obtain a carbon nanotube / modified polyethersulfone composite material; Wherein, the preparation of modified polyether sulfone comprises the following steps: Mix biphenol, allyl bromide, N,N-dimethylformamide and potassium carbonate, react, wash, filter and dry after the reaction to obtain a reaction product; continue to react the reaction product, recrystallize, filter and dry after the reaction to obtain alkenyl biphenol; The alkenyl biphenol, biphenol, pyrenyl difluorodiphenyl sulfone, potassium carbonate, N-methyl pyrrolidone and toluene are mixed and stirred, reacted, and after the reaction is completed, the reaction is continued. After the reaction is completed, the modified polyether sulfone is obtained; the mass ratio of alkenyl biphenol, biphenol, pyrenyl difluorodiphenyl sulfone, potassium carbonate, N-methyl pyrrolidone and toluene is 1.8-2.2:5.6-5.9:18-18.2:5.8-6:50-60:25-30; the reaction conditions are: reacting at a temperature of 130-140°C for 3-4h in a nitrogen atmosphere; the continued reaction conditions are: continuing the reaction at a temperature of 160-170°C for 10-14h; Step (2), mixing silicon carbide nanowires, ethanol, and titanate silane coupling agent, dispersing by ultrasonication, reacting, filtering, washing, and drying after the reaction is completed to obtain modified silicon carbide nanowires; The mass ratio of silicon carbide nanowires, ethanol and titanate silane coupling agent is 10:300-350:0.8-1; the reaction conditions are: reacting at 80-100°C for 1-2h; The modified silicon carbide nanowires, polytetrafluoroethylene powder, silicone resin, carbon nanotube / modified polyethersulfone composite material and polyetheretherketone are uniformly mixed, reacted, melt-extruded and granulated to obtain a corrosion-resistant, high-temperature-resistant and high heat transfer material based on polyetheretherketone.
2. The method for preparing a corrosion-resistant, high-temperature-resistant and high heat transfer material based on polyetheretherketone according to claim 1, characterized in that: In the step (1), the mass ratio of modified polyethersulfone, chloroform, methanol and carbon nanotube suspension is 10:140-150:1-1.8:18-20, and the carbon nanotube suspension is prepared by mixing carbon nanotubes and chloroform in a mass ratio of 1:5; the stirring and mixing conditions are: stirring and mixing at a speed of 250-300 r / min for 0.5-1h.
3. The method for preparing a corrosion-resistant, high-temperature-resistant and high heat transfer material based on polyetheretherketone according to claim 1, characterized in that: When preparing the modified polyethersulfone in step (1), in the preparation of alkenyl biphenol: The mass ratio of biphenol, allyl bromide, N,N-dimethylformamide and potassium carbonate is 18-19:25-28:380-430:50-55; the reaction conditions are: react at 100-110°C for 8-10h; the continued reaction conditions are: react in a nitrogen atmosphere at 208-210°C for 0.5-1h.
4. The method for preparing a corrosion-resistant, high-temperature-resistant and high heat transfer material based on polyetheretherketone according to claim 1, characterized in that: When the modified polyether sulfone is prepared in step (1), the pyrene difluorodiphenyl sulfone comprises the following steps: Mixing 4,4'-difluorodiphenyl sulfone with concentrated sulfuric acid, adding N-bromosuccinimide, reacting, purifying and drying after the reaction is completed, to obtain bromodifluorodiphenyl sulfone; Bromodifluorodiphenyl sulfone, 1-pyrene boric acid, potassium phosphate, palladium acetate, triphenylphosphine and toluene are mixed and reacted. After the reaction is completed, the solvent toluene is removed by rotary evaporation to obtain a reaction product, and the organic phase is extracted and passed through a column to obtain pyrene difluorodiphenyl sulfone.
5. The method for preparing a corrosion-resistant, high-temperature-resistant and high heat transfer material based on polyetheretherketone according to claim 4, characterized in that: In the preparation of the pyrenyl difluorodiphenyl sulfone, the mass ratio of 4,4'-difluorodiphenyl sulfone, concentrated sulfuric acid and N-bromosuccinimide is 1.2-1.25:45-46:1.9-1.95, and the concentrated sulfuric acid is 98wt% concentrated sulfuric acid; the addition time of N-bromosuccinimide is to add it in batches within 2-3h; when preparing brominated difluorodiphenyl sulfone, the reaction conditions are: react at room temperature for 6-8h; the mass ratio of brominated difluorodiphenyl sulfone, 1-pyrene boric acid, potassium phosphate, palladium acetate, triphenylphosphine and toluene is 5.3-5.5:8.3-8.5:11-12:0.3-0.31:0.7-0.71:60-80; when preparing pyrenyl difluorodiphenyl sulfone, the reaction conditions are: react at a temperature of 90-100°C for 20-24h.
6. The method for preparing a corrosion-resistant, high-temperature-resistant and high heat transfer material based on polyetheretherketone according to claim 1, characterized in that: In the step (2), the mass ratio of modified silicon carbide nanowires, polytetrafluoroethylene powder, silicone resin, carbon nanotube / modified polyethersulfone composite material, and polyetheretherketone is 10-15:10-12:3-5:10-15:110; the reaction conditions are: reacting at a temperature of 345-350°C for 30-40min; and the melt extrusion conditions are: melt extrusion through a twin-screw extruder at a speed of 150-160r / min and a temperature of 355-365°C.
7. A corrosion-resistant, high-temperature-resistant, high-heat-transfer material based on polyetheretherketone prepared by the method for preparing a corrosion-resistant, high-temperature-resistant, high-heat-transfer material based on polyetheretherketone as claimed in any one of claims 1 to 6.
8. Use of the corrosion-resistant, high-temperature-resistant and high heat transfer material based on polyetheretherketone as claimed in claim 7 in a mold.
Citation Information
Patent Citations
High-heat-conductivity polyether ether ketone composite material and preparation method thereof
CN107459770A
Pyrene content precisely controlled side chain pyrene containing polyarylether polymer and preparation method thereof
CN106084206A
High impact polyaryletherketone - polycarbonate blends
CN108350261A